Tingkat Agresivitas Dan Power Atlet Karate Pada FORKI Kabupaten Jepara - Ridha Aulliyya Ainur Ramadhani; Donny Wira Yudha Kusuma; Ipang Setiawan; Wahyu Ragil Kurniawan (Universitas Negeri Semarang, 2024)
The background of this study is FORKI as the basis for sports coaching to produce outstanding karate athletes. Achievement itself is influenced by many factors, one of which is psychological personality. Sports psychology requires personality to understand the personality characteristics of an athlete. This study aims to measure the level of aggressiveness and power of Karate Athletes in Forki Jepara Regency. This survey was conducted using a quantitative approach method. In this study, 17 PPAP athletes from Jepara Regency will be used as samples through purposive sampling techniques. As a data collection instrument, the author used the SPQ20 questionnaire which was disseminated online via a goog;e form consisting of 168 questions that looked at various elements such as achievement and competition, belief and toughness, interaction and sportsmanship, aggressiveness and power. The results of the research obtained for male and female athletes are in the same item, namely Aggressiveness has a score of 205 with an average of 3.66. Meanwhile, femaleathletes have a score of 270 with an average of 3,375. And Power has a score of 124 with an average of 3.54. Meanwhile, female athletes have a score of 174 with an average of 3.48. It can be concluded that the level of aggressiveness and power of karate athletes in FORKI Jepara Regency is high